Characteristics and Clinical Significance of Gut Microbiota in Patients with Invasive Pulmonary Aspergillosis - CAO JIAQI; HE QIAN; ZHANG MING; ZHOU RONG; FENG CHUNLAI (Polish Journal of Microbiology)
Gut microbiota acts on the lungs through the gut-lung axis and play an important role in lung diseases. However, there are no reports on the gut microbiota characteristics in patients with invasive pulmonary aspergillosis (IPA). We aimed to analyze changes in gut microbiota in IPA patients, correlate these changes with clinical indicators and disease prognosis, and explore the application value of these characteristic changes in diagnosing IPA. The objective was to provide a theoretical basis for preventing and treating individual immunity. We conducted metagenomic next-generation sequencing of fecal samples from 43 patients with IPA and 31 healthy controls to analyze changes in the gut microbiota of these patients. We also built a random forest model for diagnosing IPA based on the gut microbiota. Compared to healthy controls, IPA patients showed a decrease in gut microbiota diversity and metabolic levels. Changes in the microbiota were characterized by a significant reduction in anti-inflammatory species that produce short-chain fatty acids, such as Faecalibacterium, Blautia, Roseburia, Phocaeicola, and Bacteroides. In contrast, opportunistic pathogens, such as Enterococcus, Corynebacterium, Escherichia, Staphylococcus, Haemophilus, and Finegoldia, were significantly enriched. The classification model based on Clostridium fessum, Blautia wexlerae, Streptococcus pseudopneumoniae, Corynebacterium striatum, and Faecalibacterium prausnitzii showed high value in distinguishing patients with IPA from healthy controls. Patients with IPA exhibit gut microbiota imbalance. The gut microbiota can serve as a biomarker that helps in diagnosing IPA. Our findings support the potential use of gut microbiota as a target for IPA prevention and treatment.